Trials using different hook and bait types in the configuration of the surface longline gear used by the Spanish swordfish (Xiphias gladius) fishery in the Atlantic Ocean - Mejuto-García, Jaime; García-Cortés, Blanca; Ramos-Cartelle, Ana (2008)
Three types of hooks and baits were tested on two swordfish longliners over a period of 480 days at sea in five zones of the North and South Atlantic Ocean. Nominal CPUE data would suggest that the overall catch rates in weight of the fish species in general were reduced with the alternate hooks and baits tested. Overall rates (+7% and –8%) and (+3% and –11%) were found for the swordfish and blue shark, respectively in relation to the hook and bait combination of reference. The shortfin mako exhibited substantial decreases (–9% and –61%). For the billfish group, however, the all rates underwent an increase (+7% and +49%). For the sea turtle species CAT (Caretta caretta)and LOL (Lepidochelys olivacea), the nominal catch rates using alternate hooks and baits tested were generally found to increase (+2%, +557%) and (+203%, –66%), respectively. Standardized log normal CPUEs showed that “zone” was the most important significant factor explaining the variability in the CPUE of all the species. “Hook type” was only significant in the billfish group, while “bait type” proved to be significant for the shortfinmako, several other fish and the sea turtleC. caretta. The interaction between bait and other factors were also significant for some species. The mean standardized CPUE data also suggest that the use of alternative hooks could cause variations in the CPUE of swordfish (+14% and – 11%) depending on the type of bait combined. The circle hook would lead to losses for this species (– 11% and –1%) depending on the type of bait combined. A comparison of the standardized CPUEs would suggest that changing the hook and maintaining the same type of bait could result in an increase in the level of sea turtles by-catch that become hookedin external or internal locations. The use of squid as bait instead of mackerel would cause a considerable increase in the number of some species of sea turtles being hooked either externally or internally, regardless of the type of hook used. No seabird interaction occurred during the whole ...